Prevention of Bullying Through Education of MIN 3 Students in Lhokseumawe City - Zahara, Cut Ita; Dewi, Rahmia; Aulia, Cut Azizul; Amelia, Isnaini; Panggabean, Syahnaz Mardhatillah (HM Publisher, 2023)
Bullying literally in Indonesian means a bully, a person who likes to annoy the weak. This study aims to describe educational outreach activities related to bullying prevention for MIN 3 students in Lhokseumawe City. The learning approach used in this activity is by using a discussion forum. This activity has received permission from the Principal of MIN 3 Lhokseumawe City and the local Education Office. The material provided in this education is in the form of understanding bullying and how to respond to bullying in the environment. The delivery method used is an interactive method with more discussion and sharing. After the presentation of the material, a simple evaluation was carried out regarding the participants' understanding of the material. In conclusion, bullying prevention education activities are very useful in increasing children's understanding of avoiding bullying activities.